2014
DOI: 10.1101/gr.177220.114
|View full text |Cite
|
Sign up to set email alerts
|

Megabase-scale deletion using CRISPR/Cas9 to generate a fully haploid human cell line

Abstract: Near-haploid human cell lines are instrumental for genetic screens and genome engineering as gene inactivation is greatly facilitated by the absence of a second gene copy. However, no completely haploid human cell line has been described, hampering the genetic accessibility of a subset of genes. The near-haploid human cell line HAP1 contains a single copy of all chromosomes except for a heterozygous 30-megabase fragment of Chromosome 15. This large fragment encompasses 330 genes and is integrated on the long a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(225 citation statements)
references
References 44 publications
(59 reference statements)
6
207
0
3
Order By: Relevance
“…HAP1 cells have a haploid karyotype except for a fragment of chromosome 15, which is located in chromosome 19, and these cells also contain a reciprocal translocation between chromosomes 9 and 22 (36,37). None of these features affects the structures of the three genes ATP5G1, ATP5G2, and ATP5G3 encoding the three different precursors of the c-subunit of ATP synthase, which are found, respectively, on the single-copy chromosomes 17, 12, and 2.…”
Section: Resultsmentioning
confidence: 99%
“…HAP1 cells have a haploid karyotype except for a fragment of chromosome 15, which is located in chromosome 19, and these cells also contain a reciprocal translocation between chromosomes 9 and 22 (36,37). None of these features affects the structures of the three genes ATP5G1, ATP5G2, and ATP5G3 encoding the three different precursors of the c-subunit of ATP synthase, which are found, respectively, on the single-copy chromosomes 17, 12, and 2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to generating gene knockouts, the CombiGEM-CRISPR platform could be used for high-order combinatorial gene activation and repression studies by incorporating gRNAs and deactivated Cas9 variants repurposed as transcriptional and epigenetic regulators (8,9,51,52). This technology could also be used to interrogate the function of large genomic deletions (53) and rearrangements (54,55) with barcoded gRNA pairs. Thus, CombiGEM-CRISPR provides a facile approach to uncover gene and drug combinations that exert desired biological responses, especially for phenotypes that require more than a single perturbation to be manifested due to underlying complex biological networks.…”
Section: Discussionmentioning
confidence: 99%
“…First proof-of-principle studies showed that Cas9 can be successfully targeted to endogenous genes in bacteria (12), human pluripotent stem cells (13), as well as in whole organisms such as zebrafish (14), yeast (15), fruit flies (16), mice (17), rats (18) and rabbits (19). In addition, a haploid human cell line named engineered-HAPloid cells has been generated by megabase-scale deletion using CRISPR/Cas9 (20).…”
Section: Introductionmentioning
confidence: 99%